The Influence of Food Reviewers on Purchase Intention toward Halal Food among Generation Z in Banda Aceh, with User Interaction as a Mediating Variable - Haya Thaharah Zulza; Ahmad Nizam; Khairil Umuri (International Journal of Kita Kreatif, 2026)
The high spending of Gen Z in Indonesia on food and daily necessities, as well as the considerable amount spent on internet access and phone bills as key monthly expenses, reflects change in their consumption behavior toward basic needs and digital access. This study aims to examine the influence of food reviewers on the purchase intention of halal culinary products among Gen Z in Banda Aceh, with user interaction as a mediating variable. This study used a quantitative method with 100 Gen Z of Banda Aceh City, selected using purposive sampling technique. Data was analyzed using Smartpls 4. The research results shown that food reviewers have a significant effect on user interaction but do not have a direct significant effect on purchase intention. Additionally, user interaction has a significant effect on purchase intention and mediates the relationship between food reviewers and purchase intention. These findings demonstrate that user interaction plays an important role in increasing the purchase intention of halal culinary products among Gen Z in Banda Aceh, providing direction for businesses and food reviewers to develop strategies that can strengthen user interaction and create more effective promotional impact.